Chapter Introduzione - CAMPUS, MAURO (Studi e saggi, 2022)
Taxation is what the European Union lacks today. EU is an area of rights without duties or, rather, in which duties (including taxation) exist only vis-à-vis the individual member states to which they belong. European citizenship is therefore halved, because it is indistinguishable from national citizenship and does not express solidaristic belonging to a supranational community. The investigation into the Union's own tax is the means to address broader issues related to the being of the European Union and its citizens and having at their core the transnational declination of solidarity. The economic and financial profile - inextricably linked to the tax and its revenue - transcends into the centrality of the uses, i.e. the goods and services that the Union may be able to provide, and the indispensable overcoming of the national particularisms that this implies.